2002
DOI: 10.1016/s1010-7940(02)00121-5
|View full text |Cite
|
Sign up to set email alerts
|

Early extubation does not increase complication rates after coronary artery bypass graft surgery with cardiopulmonary bypass

Abstract: The study shows that a very fast track extubation protocol may be safely implemented in patients submitted to coronary artery bypass graft surgery with cardiopulmonary bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 21 publications
2
51
0
6
Order By: Relevance
“…27,28 Fentanyl at a dose of 10 to15 μg/kg at induction is commonly used in many centers. 2,16,17,28,24,26,30 Remifentanil was equally safe and effective as fentanyl with no difference in time to extubation. 21 We have maintained anaesthesia with propofol, isoflurane combination in the pre by-pass period.…”
Section: Methods Of Ftcamentioning
confidence: 93%
See 2 more Smart Citations
“…27,28 Fentanyl at a dose of 10 to15 μg/kg at induction is commonly used in many centers. 2,16,17,28,24,26,30 Remifentanil was equally safe and effective as fentanyl with no difference in time to extubation. 21 We have maintained anaesthesia with propofol, isoflurane combination in the pre by-pass period.…”
Section: Methods Of Ftcamentioning
confidence: 93%
“…We have included combination of low dose propofol, ketamine, midazolam as induction agent, fentanyl as opioid and vecuronium as muscle relaxant. The most common induction agent is propofol in combination with an opioid, usually at a dose of 0.5 mg/kg with 10mg boluses until loss of consciousness 17,21,22,23,24 although some use propofol in higher doses 2,5,25 or even start directly with an infusion. 26 Etomidate, thiopentone and ketamine are described as being used.…”
Section: Methods Of Ftcamentioning
confidence: 99%
See 1 more Smart Citation
“…Early extubation plays a significant role in FTCA Potential benefits of early extubation include the rapid normalization of ciliary function, an earlier ability to cough, a reduction in the risk of atelectasis, and the correction of intrapulmonary shunt fraction. Cheng et al [4] and Reis et al [5] reported on the safety and efficacy of early extubation. The most important step is the use of minimal doses of (or the titration of) short-acting opioids with inhalation anesthetic agents.…”
Section: Discussionmentioning
confidence: 99%
“…14 The rapid postoperative rehabilitation procedure that is mandatory for the success of fast-track management (early ambulation after tracheal extubation, followed by transfer to the ward within several hours and full mobilization on the same day) 9 requires optimal pain management. For fast-tracking, administration of opioids, the mainstay of postoperative analgesia, via the standard iv or patient-controlled route 15,16 is unfeasible.…”
Section: Discussionmentioning
confidence: 99%